2020
DOI: 10.48550/arxiv.2006.14198
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Simple Approach to Case-Based Reasoning in Knowledge Bases

Abstract: We present a surprisingly simple yet accurate approach to reasoning in knowledge graphs (KGs) that requires no training, and is reminiscent of case-based reasoning in classical artificial intelligence (AI). Consider the task of finding a target entity given a source entity and a binary relation. Our non-parametric approach derives crisp logical rules for each query by finding multiple graph path patterns that connect similar source entities through the given relation. Using our method, we obtain new state-of-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 16 publications
(24 reference statements)
0
4
0
Order By: Relevance
“…We found that 76.5% (88) indications were "reported" in the literature and 5.2% (6) were "side-effects" and 18.3% (21) as "no prior link" for TransE. For probCBR, we found 73% (84) were "reported", 6.1% (7) were "side-effects" and 20.9% (24) as "no prior link". Plausible predictions from combining TransE and probCBR can be seen in Table III.…”
Section: Select Diseases For Annotationmentioning
confidence: 74%
See 2 more Smart Citations
“…We found that 76.5% (88) indications were "reported" in the literature and 5.2% (6) were "side-effects" and 18.3% (21) as "no prior link" for TransE. For probCBR, we found 73% (84) were "reported", 6.1% (7) were "side-effects" and 20.9% (24) as "no prior link". Plausible predictions from combining TransE and probCBR can be seen in Table III.…”
Section: Select Diseases For Annotationmentioning
confidence: 74%
“…Finally, the paths obtained are applied to the query entity h q to identify the answer. When multiple answers arise, the answers are ranked by the frequency of paths that lead to them [24]. Probabilistic case based reasoning extends the original case based reasoning method by improving the identification of similar entities with k-nearest neighbors approach, and by creating a probabilistic model that estimates the likelihood a retrieved path leads to a correct answer given query relation [30].…”
Section: Knowledge Graph Completion Methods For Drug Repositioningmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, CBR has been successfully applied in the field of knowledge-based reasoning Das et al (2020). andDas et al (2021) show that CBR can effectively learn to generate new logical reasoning chains from prior cases, to answer questions on knowledge graphs.…”
mentioning
confidence: 99%